2008
DOI: 10.1093/ee/37.5.1214
|View full text |Cite
|
Sign up to set email alerts
|

Carabid Assemblages (Coleoptera: Carabidae) in a Rotation of Three Different Crops in Southern Alberta, Canada: A Comparison of Sustainable and Conventional Farming

Abstract: Carabids were sampled in 2000 (pretreatment year) and 2003-2005 in experimental plots in southern Alberta, Canada, after a rotation of beans, wheat, and potato under sustainable and conventional farming practices. Each phase of the rotation was present in every year. Crop type had a stronger effect than sustainable treatment on carabid-expected species richness, diversity, and species composition. However, carabid activity density was consistently higher in plots under sustainable treatments than those maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Potato plots had lower carabid activity density than wheat and bean plots, but the crops did not differ in terms of diversity, and there were species-specific responses to crop species (Bourassa et al 2008). However, other agricultural practices and inputs varied between the crops in the rotation, confounding the results (Bourassa et al 2008).…”
Section: Vegetation Structure: Crop Rotationmentioning
confidence: 99%
See 4 more Smart Citations
“…Potato plots had lower carabid activity density than wheat and bean plots, but the crops did not differ in terms of diversity, and there were species-specific responses to crop species (Bourassa et al 2008). However, other agricultural practices and inputs varied between the crops in the rotation, confounding the results (Bourassa et al 2008).…”
Section: Vegetation Structure: Crop Rotationmentioning
confidence: 99%
“…Insecticide use generally decreases the activity and density of carabids (Floate et al 1989;Bourassa et al 2008). In a crop rotation study, Bourassa et al (2008) observed that the activity density of carabid species, based on pitfall trap data, was significantly less in the insecticide treated potato crop relative to other crops in the rotation that received no insecticides.…”
Section: Agricultural Inputs and Practices: Abiotic Factors That Affementioning
confidence: 99%
See 3 more Smart Citations